AN SECURE EFFECTIVE GREEN MECHANISM FOR BUDGET DECLINE IN CLOUD (Global Journal of Advanced Engineering Technologies and Sciences, 2017)
Cloud computing is a new paradigm for delivering remote computing resources through a network. However, achieving an energy efficiency control and simultaneously satisfying a performance guarantee have become critical issues for cloud providers. In this paper, three power-saving policies are implemented in cloud systems to mitigate server idle power. The challenges of controlling service rates and applying the N-policy to optimize operational cost within a performance guarantee are first studied. A cost function has been developed in which the costs of power consumption, system congestion and startup are all taken into consideration. The effect of energy-efficiency controls on response times, operating modes and incurred cost are all demonstrated. Our objectives are to find the optimal service rates and mode-switching restriction, so as to minimize cost within a response time guarantee under varying arrival rates. An efficient green control algorithm is first proposed for solving constrained optimization problems and making cost/performances tradeoffs in systems with different power saving policies. Simulation results show that the benefit of reducing operational costs and improving response times can be verified by applying the power saving policies are combined with the proposed algorithm as compared to a typical system under a same.